Analisis Makna Distribusi Kekayaan Perspektif Ekonomi Islam dalam Pandangan Al-Qur’an dan Hadits - Syahrul Amsari; Sugianto Sugianto; Ahmad Afandi; Asmaul Husna (Ekonomis: Journal of Economics and Business, 2023)
The distribution of wealth is the center of attention of Islamic economics to achieve common prosperity. The purpose of this study is to find out how the concept of good and correct distribution of wealth in the Islamic economy is based on the Al Qur’an and Hadith. This research is a library research where data sources are taken from books, hadith books, journals and others using the maudhu'i interpretation method or better known as thematic interpretation and all data is reviewed and described into a systematic discussion. This shows that the concept of wealth distribution which is prohibited by Allah in the Qur'an is the circulation of wealth that occurs only to a group of people. The existing reality shows that there are still many people who use the wrong concept of distribution. So that the rich remain rich and the poor remain poor, while the correct distribution of wealth is when the circulation of wealth does not only occur in certain circles. As in the interpretation of QS. Al Hasry verse 7 then in solving this problem, it is necessary to have an economic mechanism and a non-economic mechanism to overcome the wrong concept of distribution, so that it can produce a complete concept from the Al Qur’an on this problem, so that the distribution of wealth will circulate to all groups and will not occur social inequality in society.